A Survey of the Knapsack Problem - Haraty, Ramzi A. (2019)
The Knapsack Problem (KP) is one of the most studied combinatorial problems. There are many variations of the problem along with many real life applications. KP seeks to select some of the available items with the maximal total weight in a way that does not exceed a given maximum limit L. Knapsack problems have been used to tackle real life problem belonging to a variety of fields including cryptography and applied mathematics. In this paper, we consider the different instances of Knapsack Problem along with its applications and various approaches to solve the problem.